If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = -14 + -8x Reorder the terms: 8 + 3x = -14 + -8x Solving 8 + 3x = -14 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 8 + 3x + 8x = -14 + -8x + 8x Combine like terms: 3x + 8x = 11x 8 + 11x = -14 + -8x + 8x Combine like terms: -8x + 8x = 0 8 + 11x = -14 + 0 8 + 11x = -14 Add '-8' to each side of the equation. 8 + -8 + 11x = -14 + -8 Combine like terms: 8 + -8 = 0 0 + 11x = -14 + -8 11x = -14 + -8 Combine like terms: -14 + -8 = -22 11x = -22 Divide each side by '11'. x = -2 Simplifying x = -2
| 2x+8=92-8x | | 2x+10=90-6 | | 162-3x=24x+24 | | 4x-36=2x+10 | | 5x+33=7x+13 | | 6-8x=94-36x | | 29+x=10 | | x+42=41 | | 6-8x=94-39x | | 5x-17=23 | | a-10=27 | | k+3=21 | | n-34=-23 | | 8x+18=5x+6 | | 10=x+17+2x+16 | | y-41=112 | | v+36=85 | | b+8=-25 | | 6x+18=5x+7 | | 6y^2=11y+7 | | 14+y=67 | | 9x+15=6x+57 | | 14+y= | | 2x-5yi=12+15i | | 10-10x=18-17x | | 60-3x=6x+19 | | 55-4x=32x+15 | | (x-5)=8 | | 12+6=9x+24 | | 4=n-(-3) | | 10-9x=210-44x | | 9n=8n+16 |